The Effectiveness of Executive Function Training on the Dimensions of Metacognition in Students with Learning Disabilities - Bahrami, Negin; Taghinezhad, Nooshin (Psychological Research in Individuals with Exceptional Needs, 2025)
This study aimed to investigate the effectiveness of executive function training on improving the dimensions of metacognition—positive beliefs about worry, thought controllability, cognitive uncertainty, need to control thoughts, and cognitive self-consciousness—among elementary students with specific learning disabilities in Bandar Abbas. This quantitative study employed a semi-experimental pretest–posttest design with a control group and a two-month follow-up. The statistical population included all elementary school students with learning disabilities in Bandar Abbas during the 2024–2025 academic year. Thirty students from the fifth and sixth grades were purposefully selected and randomly assigned to experimental and control groups (15 students each). The experimental group received ten sessions of executive function training, focusing on planning, self-monitoring, reflection, and cognitive flexibility, while the control group received no intervention. Data were collected using the Wells Metacognition Questionnaire (MCQ-30) and analyzed using descriptive statistics and multivariate covariance analysis (MANCOVA) with SPSS version 22. The results of MANCOVA showed a significant multivariate effect of the group on the combined metacognitive variables (Wilks’ Lambda = 0.461, F = 4.440, p = 0.008, η² = 0.539). Univariate analyses indicated significant group differences in all metacognitive subscales at the posttest stage: positive beliefs about worry (F = 10.898, p = 0.003, η² = 0.322), thought controllability (F = 6.335, p = 0.019, η² = 0.216), cognitive uncertainty (F = 4.987, p = 0.036, η² = 0.178), need to control thoughts (F = 9.688, p = 0.005, η² = 0.296), and cognitive self-consciousness (F = 5.892, p = 0.023, η² = 0.204). Executive function training significantly enhanced metacognitive abilities in students with learning disabilities, improving their self-regulation, cognitive control, and reflective awareness. Integrating such interventions into educational programs may promote cognitive flexibility and academic adaptation in children with learning challenges.